Pergolakan antarabangsa : perkembangan dan isu utama sejak 1945 - Chamil Wariya, Datuk, 1952- (Kuala Lumpur : AMK Interaksi, 1989)
Impact of international political affairs in Malaysia; collection of articles.
Bibliograpfi : p.207-209
Keywords: Malaysia -- Politics and government; Malaysia -- Foreign relations